ASSESSING CRITICAL CARE NURSES’ KNOWLEDGE ON OXYGEN THERAPY IN COVID-19 PATIENT CARE IN TURKIYE; A MULTICENTER STUDY - Yasemin Uslu; Meltem Altay (Sabiad)
Objective: Oxygen therapy for individuals with COVID-19 includes best practices for supportive management of acute respiratory syndrome. The aim of this study was to determine critical care nurses’ levels of knowledge on oxygen therapy during the COVID-19. Method: This was a descriptive study. The study was conducted with COVID-19 critical care nurses (N=446) in a total of 16 hospitals affiliated with a healthcare group in Turkey. A total of 322 nurses were included in the study. The data were collected via the Oxygen Therapy Information Form prepared based on the literature through Google survey. Results: According to the oxygen therapy subscales, the mean score of the nurses varied from 40.77 to 86.21, and their total mean score was 72.99 (fairly). The nurses’ knowledge on oxygen therapy was strongly correlated with their educational level and manner of work (p<0.05). Conclusions: It can be asserted that in oxygen therapy, their knowledge on nursing interventions was adequate; however, their knowledge on oxygen therapy definitions and concepts was inadequate. In order to develop patient safety concerning oxygen therapy in COVID-19 patients, it is recommended that training programs be planned and competencies of nurses be assessed. In order to qualify legal competence about the safe oxygen therapy, clear protocols and professional guidelines are recommended.